Housing Finance in the CEMAC Region : Current Status, Opportunities, and a Way Forward for Affordable Housing - World Bank Group (World Bank, Washington, DC, 2020)
The Central African Economic and Monetary Community (CEMAC), which consists of Cameroon, the Central African Republic, Chad, the Republic of Congo, Equatorial Guinea, and Gabon, is one of the oldest regional groupings in Africa. Urbanization and growing population will put increasing pressure on existing housing resources. Without a step change in the level of housing construction and the necessary long-term finance to invest, slums will proliferate as short-term solutions fill the gap. The State is often the biggest actor in the sector with programs which are often costly and ineffective. CEMAC’s housing value chain displays high levels of dysfunction on both demand and supply sides. The enabling environment creates significant challenges in addressing the affordable housing challenge. A comprehensive and far reaching program of reforms will be needed across multiple sectors to create the conditions under which private sector investment can thrive and be properly channeled into housing investment. Lack of long-term finance is a key constraint preventing long term investment into housing. This report focuses on the road map and recommendations for development of housing in the CEMAC region.